2016
DOI: 10.3892/mmr.2016.5815
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of G9a inhibitor BIX-01294 acting on U251 glioma cells

Abstract: The present study aimed to investigate the differential expression and clinical significance of histone methyltransferase G9a, histone H3K9me2 and histone H3K9me1 in human brain glioma and adjacent tissue samples. It also aimed to observe the effect and mechanism of BIX-01294, as an inhibitor of methyltransferase G9a, on the proliferation, apoptosis, methylation of H3K9 and H3K27, and the acetylation in U251 glioma cells in vitro. The differential expression of methyltransferase G9a, histone H3K9me2 and histon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Previous studies have reported that 5 μM BIX inhibited the proliferation and induced apoptosis through downregulation of Bcl-2 expression and upregulation of Bax expression in U251 glioma cells 29 . However, twofold higher concentrations of BIX treatment did not modulate Bcl-2 expression in Caki cells (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have reported that 5 μM BIX inhibited the proliferation and induced apoptosis through downregulation of Bcl-2 expression and upregulation of Bax expression in U251 glioma cells 29 . However, twofold higher concentrations of BIX treatment did not modulate Bcl-2 expression in Caki cells (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Knockdown of the G9a gene induces chromosome instability and suppresses cancer cell proliferation and invasion, supporting the notion that G9a is a promising drug target [18][19][20]. G9a inhibitors, such as UNC0638 and BIX-01294, can inhibit cell proliferation by inducing cell cycle arrest, triggering apoptosis, or inducing autophagic cell death [21][22][23]. However, UNC0638 is not suitable for animal studies due to its poor pharmacokinetic properties [24].…”
Section: Introductionmentioning
confidence: 87%
“…Inhibiting the activities of histone methyltransferases or HDACs can suppress glioma cell proliferation and induce apoptosis (Sharma et al, 2010 ; Vargas et al, 2014 ), suggesting that the inhibitors of these proteins could be candidate drugs for the treatment of glioma. Recently, Ghildiyal and Sen ( 2017 ) reported that histone methyltransferase G9a that regulated H3K9 dimethylation has also correlated with the development and progression of glioma, and its inhibitors have also been reported as potential agents for the treatment of glioma (Guo et al, 2016 ).…”
Section: Histone Modificationsmentioning
confidence: 99%